Urban Land Value Estimation Model based on Income Capitalization Method - Sugito Nanin Trianawati; Affriani Asri Ria; Ramadhani Anisa Nabila Rizki (E3S Web of Conferences)
Land valuation is a critical component of the cadastral system, closely linked to land use and management. The value of land is typically assessed based on the benefits it offers. The high land prices often observed in urban areas result from increased demand, whereas the availability of land remains fixed. Several methods can be employed for land valuation, including the market comparison method, the income capitalization method, and the cost method. This study focuses on the income capitalization approach for determining land value. According to this method, higher income generated from a property leads to a higher property value. For residential properties, income is derived from net rent, calculated as rental income minus operational expenses, using the income approach. This research employs geostatistical analysis to model land values. The mathematical model developed through geostatistical analysis aims to represent actual land values accurately and facilitate the establishment of land value zones.